2012
DOI: 10.1177/0022022112466941
|View full text |Cite
|
Sign up to set email alerts
|

Wisdom and Ego-Identity for Korean and American Late Adolescents

Abstract: Overcoming identity crises during adolescence may help adolescents understand the world around them. Although adolescents may have developmental potential for wisdom, little is known about the direct relationship between wisdom and ego-identity or any cross-cultural effects. Wisdom dimensions (cognitive, affective, and reflective) and ego-identity statuses (achievement, moratorium, foreclosure, and diffusion) among 639 Korean and American late adolescents (aged 18 to 22) were investigated. The findings suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 53 publications
8
16
0
1
Order By: Relevance
“…However, compared with the middle school students in Deng and Roosa's study, the results of our study showed that the older the students (college students in this study) are the less likely they are to be in foreclosure status. This result is consistent with the author's previous study (Bang & Montgomery, ), which showed that although identity development is elusive, one significantly consistent result is that foreclosure decreases with age.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, compared with the middle school students in Deng and Roosa's study, the results of our study showed that the older the students (college students in this study) are the less likely they are to be in foreclosure status. This result is consistent with the author's previous study (Bang & Montgomery, ), which showed that although identity development is elusive, one significantly consistent result is that foreclosure decreases with age.…”
Section: Discussionsupporting
confidence: 93%
“…Reflective wisdom can include Chinese values such as righteousness, humanness, etiquette, and integrity as these values require constant reflective, metacognitive, and perspective‐taking abilities. While this study pinpointed the specific indicator, wisdom predicting identity achievement is a finding similar to the Korean data in the author's previous study (Bang & Montgomery, ). This is also similar to Beaumont's and Webster's studies on North American samples (Beaumont, , ; Webster, ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Pada umumnya penelitian tentang pembentukan identitas yang mempertimbangkan konteks dilakukan secara lintas negara (misalnya Bang & Montgomery, 2013;Busch & Hofer, 2011;Eryigit & Kerpelman, 2011) maupun hanya di suatu negara tertentu (misalnya Laghi, Baiocco, Liga, Guarino, & Baumgartner, 2013;Lee & Beckert, 2012;Wängqvist & Frisén, 2013). Pada penelitian ini, kami mencoba untuk memahami pembentukan identitas remaja pada konteks Indonesia khususnya di Yogyakarta.…”
unclassified
“…They theorized and applied ego identity stages and statuses among young and late adolescents _a critical period in which senses of growth, individuation, connectedness, and affirmed commitment and exploration take place. Waterman (1982) acknowledged that the nature of the social expectations related to identity choices arising within the family, the schools, and the peer group will contribute to the particular identity development pathways employed but among substantial studies deployed on timing, direction, development, antecedent conditions, age, and gender differences on identity formation, (Bang, 2002;Bradley & Matsukis, 2000;Knafo et al 2004;Kumru & Thompson, 2003; but more poor application of stressful concept tasks was observed. Beginning in the 1970s Waterman and Geary and Waterman (1974) in longitudinal investigations found the identity achievement and moratorium statuses to increase and the foreclosure and diffusion statuses to decrease in frequency over time across both vocational and ideological domains.…”
Section: Introductionmentioning
confidence: 99%